1994
DOI: 10.1007/bf00399794
|View full text |Cite
|
Sign up to set email alerts
|

The potential contribution of endothelin-1 to neurovascular abnormalities in streptozotocin-diabetic rats

Abstract: Summary Abnormal vascular endothelium function may contribute to the reduced nerve perfusion implicated in the aetiology of neuropathy in diabetes mellitus. The aim was to test the hypothesis that a powerful vasoconstrictor, endothelin-1, could be involved in nerve dysfunction in streptozotocin-diabetic rats. After 6 weeks of untreated diabetes, rats were implanted with osmotic minipumps which continuously delivered the endothelin-1 antagonist, BQ-123, to the circulation via a jugular vein cannula. Sciatic mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 64 publications
1
21
0
1
Order By: Relevance
“…This was repeated at another nerve site more than 4 mm proximal or distal. Mono-or bi-exponential curves were fitted to the data by regression analysis (Prism; Graphpad, San Diego, Calif., USA) [39]. The fitting procedure gave r 2 values within the range 0.997-1.000 for all individual curves in this study.…”
Section: Methodsmentioning
confidence: 94%
“…This was repeated at another nerve site more than 4 mm proximal or distal. Mono-or bi-exponential curves were fitted to the data by regression analysis (Prism; Graphpad, San Diego, Calif., USA) [39]. The fitting procedure gave r 2 values within the range 0.997-1.000 for all individual curves in this study.…”
Section: Methodsmentioning
confidence: 94%
“…Nerve polyols nevertheless remain in the non-diabetic range, thus, a putative "pseudohypoxia" mechanism, based on changes in neuronal NADH/NAD ratio due to flux through the second half of the polyol pathway [41] is unlikely to cause the NCV reduction. Conversely, blood flow and NCV are restored by EPO and vasodilator treatments [2,4,5,19,39] although polyol pathway and pseudohypoxia mechanisms remain strongly activated. Thus, it must be concluded that pseudohypoxia does not contribute significantly to diabetic NCV changes and that neurovascular mechanisms predominate.…”
Section: Discussionmentioning
confidence: 99%
“…Endoneurial blood flow was measured in the contralateral limb by microelectrode polarography and hydrogen clearance as previously described [5,19]. Rats were given neuromuscular blockade using o-tubocurarine (Sigma, 2 mg. kg -~ via the carotid cannula) and artificially ventilated.…”
Section: Experimental Groups and Diabetes Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sciatic axons in these rats are selectively susceptible to ischaemia induced by ET-1 due to more intense and prolonged vasoconstriction to the peptide [54]. Moreover, sciatic nerve motor conduction deficits in diabetic rats were corrected by an ET A antagonist, in association with increases in sciatic nutritive endoneurial blood flow [55]. Non-selective ET A /ET B blockade failed, however, to evoke similar actions [56], indicating that the addition of ET B blockade might blunt the beneficial effects of ET A antagonism.…”
Section: In Vivo Haemodynamic Studiesmentioning
confidence: 95%